(untitled) (Research, Society and Development, 2021)
Chagas disease (CD) is transmitted by the hemoflagellate parasite Trypanosoma cruzi and manifests itself acutely and chronically, when it is characterized as indeterminate, cardiac, digestive or mixed. Some patients with Chagas’ disease (CD) have cognitive alterations and there are three hypotheses about cognitive damage: (I) neurological and cognitive alterations caused by the cardiac form, (II) after the acute form there is the spontaneous disappearance of the clinical signs of disease with cognitive manifestations remaining, (III) cognitive and neurological manifestations are caused by chronic infection. The aim of the present study was to carry out a systematic review of the literature to verify measurable cognitive impairments in Chagas patients. The articles were searched in the Pubmed and Embase databases, with the descriptors "Chagas disease" and "cognition". All articles with assessment of cognitive aspects of patients with CD were included. One hundred and ninety-seven articles were found, three of which met the criteria. All articles demonstrate cognitive impairments related to CD, in a chronic form, with impairment of both general intelligence and long-term memory, in addition to a deficit in the execution time of the tests.